Working Memory in ADHD: A Comparison of British and South African Children. (May 2014) - Alloway, Tracy P.; Cockcroft, Kate
Objective: The aim of the present study was to investigate the following issues: (a) Do students with ADHD have a pervasive pattern of impaired working memory skills across verbal and visuospatial domains? (b) is there evidence for a similar pattern of deficits across U.K. and South African students? and (c) which working memory tasks can effectively identify students with ADHD from TD peers?Method: Four groups of children participated in the study: students with ADHD and TD from the United Kingdom and students with ADHD and TD from South Africa.Results: There were several key findings. First, the students with ADHD in South Africa performed significantly worse than the other groups (ADHD-United Kingdom, TD-United Kingdom, and TD-South Africa) in verbal and visuospatial short-term memory measures. Next, students with ADHD in the United Kingdom and South Africa exhibited working memory deficits extended to the visuospatial domain. This pattern was consistent with previous research in developmental populations (Alloway et al., 2006) and in adult samples (Kane et al., 2004; Park et al., 2002). A related finding was that the memory deficits in the students with ADHD (in the United Kingdom and South Africa) were significantly worse than their TD counterparts even when IQ and age were statistically accounted. These persistent deficits fit well accumulating evidence of the importance of working memory in learning.Conclusion: Practical implications for education will be discussed in the context of appropriate diagnosis and support in the classroom.